Relationship Between Stress Levels and Sleep Quality with Hypertension Incidence in Elderly Individuals - Inggara, Rizkika Arman; Ririnisahawaitun; Sari, Apriani Susmita (Bantayang Omni Cendekia, 2024)
Background: The elderly population experiences gradual physical, mental, and social decline, increasing vulnerability to degenerative diseases such as hypertension. Elevated blood pressure in older adults is often associated with poor lifestyle choices, inadequate physical activity, poor dietary habits, stress, and sleep disturbances. Objective: This study aimed to examine the relationship between stress levels and sleep quality with the incidence of hypertension among elderly individuals in Nenggung Village, within the Masbagik Health Center's working area Methods: A cross-sectional correlational design was used. The sample consisted of elderly individuals selected through purposive sampling. Data were collected using standardized questionnaires: the Perceived Stress Scale (PSS) to measure stress levels, the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality, and medical records to confirm hypertension status. The Spearman rank correlation test was used to analyze the relationships between variables. Results: The analysis revealed a significant positive correlation between stress level and hypertension incidence (p = 0.002; r = 0.495), indicating a moderately strong relationship. A significant correlation was also found between sleep quality and hypertension incidence (p = 0.007; r = 0.448), suggesting that poor sleep quality is moderately associated with increased hypertension risk. Conclusion: Higher stress levels and poor sleep quality are significantly associated with the incidence of hypertension in the elderly. Preventive measures such as regular health monitoring, stress management, and promoting better sleep hygiene are recommended to reduce hypertension risk in this population.